Field ionization detectors: a comparative model - O'Donnell, Kane; Fahy, A.; Thomsen, L.; O'Connor, D.; Dastoor, P. (IOP Publishing Ltd, 2011)
Recently there has been renewed interest in using field ionization as a method of detecting neutral atomic/molecular species. However, the current–voltage characteristic of a field ionization detector is very difficult to calculate from first principles, making comparison, characterization and monitoring difficult. Here we present a semi-empirical theory designed for macroscopic characterization and comparison of field ionization devices via the current–voltage curve in a similar fashion to the familiar Fowler–Nordheim analysis for field emission devices. The resulting model allows us to monitor the changes in a single field ionization detector, or, more importantly, to make quantitative comparisons between detectors. We demonstrate that this new model accurately reproduces the characteristic field ionization current versus voltage profiles in both low and high field regimes.